Analisis Efektivitas Penerapan Digital Communication dalam Fundraising Yayasan Baitul Maal BRILiaN - Rahmadana, Nia; Effendi, Erwan (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2024)
Digital Communication is also utilized by various parties, including the Baitul Maal BRILiaN. This study aims to understand the effectiveness of applying digital communication in the form of a web or app that can be accessed anytime and anywhere to collect donations (collect) and then redirect the donations to the right people. This study adopted a descriptive qualitative approach. Data collection techniques were taken from interviews and literature reviews related to the title of this research paper. The results of this study show that the effectiveness of implementing digital communications in the fundraising activities of the Baitul Maal BRILiaN Foundation was assessed using effectiveness indicators, such as whether the project objectives, project outreach, project objectives, and project monitoring were effective. The community, especially those who are the program’s primary target, can donate anytime and anywhere as long as they are connected to the internet.